Statistical Modelling in Health: Some Case Studies - Henriques, Carla (2017)
This presentation focus on two examples of applications of Statistics in the field of Medicine. Research questions are posed by health professionals. The answers are not always straightforward, and the difficulties show up with different forms. In the first case study, the objective was to find a panel of biomarkers that would be useful to predict the course of a kidney disease – Immunoglobulin A nephropathy (IgAN). The study could confirm the predictive role of some of the established risk factors for disease progression and also suggests a combination of two histological biomarkers (C4d and CD3) to predict IgAN progression. In the second example we move to the area of cardiology, looking for a model that could be a valuable adjuvant in the diagnosis of Brugada Syndrome. A set of five electrocardiographic markers were identified and their linear combination was explored in order to find one that could be a reliable tool in Brugada Syndrome diagnosis. This talk is based in joint work with Ana Cristina Matos, of the Polytechnic Instituto of Viseu, Luís Ferreira dos Santos of the Tondela-Viseu Hospital Center, and Bernardo Faria of the Nephrology and Infectious Disease R&D Group, INEB, I3S, University of Porto, Porto.